1997
DOI: 10.1111/j.1600-0587.1997.tb00358.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elk on aspen in the winter range in Rocky Mountain National Park

Abstract: National parks face problems in managing wild ungulates and their forage resources, including small park sizes and incomplete protection of winter ranges, absence of major predators, and influences from extenor management activities Our study focuses on the efTects of elk Cervus elaphus browsing on aspen Populus tremuloides in the elk winter range of Rocky Mountain National Park Elk can prevent successful regeneration of aspen by suckers, and increase the monality of established trees Here we quantify the efTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 13 publications
9
106
2
Order By: Relevance
“…First, the results indicated drastically declining aspen cover in the Targhee National Forest. Similar to local-scale studies [13,15,45,46], the results indicated that 94.5% of the aspen mapped in 1920 had declined by 2005. The shorter-term change detection indicated a lesser, but still a substantial decline of 89.5%.…”
Section: Aspen Change Detectionsupporting
confidence: 75%
“…First, the results indicated drastically declining aspen cover in the Targhee National Forest. Similar to local-scale studies [13,15,45,46], the results indicated that 94.5% of the aspen mapped in 1920 had declined by 2005. The shorter-term change detection indicated a lesser, but still a substantial decline of 89.5%.…”
Section: Aspen Change Detectionsupporting
confidence: 75%
“…In Rocky Mountain National Park, Colorado, declines of willow and aspen have been documented and attributed to high ungulate populations (Olmsted 1979;Baker et al 1997;Peinetti et al 2002). Lubow et al (2002) concluded that the park population was food-limited density dependent, likely at a higher population level than achieved under natural regulation with top predators.…”
Section: Discussionmentioning
confidence: 99%
“…While aspen suckers may continue to emerge within small canopy openings, their proliferation becomes increasingly limited without larger disturbance. Survival of aspen regeneration in conifer-dominated stands is often low due to increasing resource limitations and the well documented impacts of ungulate browsing (Baker et al, 1997;Hessl and Graumlich, 2002;Kay and Bartos, 2000;Ripple et al, 2001). Moreover, reduced aspen cover has resulted in limitations on further asexual reproduction: the fewer healthy trees above ground, the less likely new suckers will emerge either on a continuous basis or in a flush following disturbance (Shepperd et al, 2006).…”
Section: Successional Trends From Aspen To Conifer Covermentioning
confidence: 99%